ANALISIS PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH KOTA MANADO TAHUN 2015 - Dini, Andi Lombar; Sabijono, Harijanto; Gerungai, Natalia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The government has the power to collect people's income and use it to finance these activities in order to provide services to the public. Governments should be responsible for such activities in a transparent manner, in accountability to make a financial report where the financial statements will be assessed by the BPK to be given an audit opinion. On Wednesday 22 June 2016, the manado city government represented by the mayor of Manado received LHP (Laporan Hasil Pemeriksaan) from the State Audit Agency Republic of Indonesia (BPK-RI) representative of North Sulawesi on the financial statements of Manado city government in 2015. However, from several studies, there are still some reports that have not fully disclosed the information that should be disclosed in the financial statements. This research method using qualitative method. The results of this study found the disclosure level of financial statements of Manado city government in 2015 was 52.94%, it explains that the financial statements of Manado municipal government have not fulfilled all the disclosure items in PP N0.71 Year 2010 on Government Accounting Standards.Keywords : Disclosure, Opinion, Public